Christology and Exegesis in the Cappadocians - Winslow, Donald F. (Church history, 1971)
When, after their decade of studies in Athens, Basil of Caesarea and Gregory of Nazianzus returned to Cappadocia, one of the first things they did was to compile a collection of the exegetical works of Origen and publish them under the title Philokalia. This fact might lead the historian to conclude that Basil and Gregory subscribed to, or at least were in sympathy with, the allegorical method of exegesis. But such is hardly the case, for in their later writings (and this holds true for the third member of the Cappadocians, the younger Gregory of Nyssa) there can be discovered no one prevailing approach to the interpretation of scripture. Allegory is indeed used, and often, but so too we find typological and anagogical exegesis, as well as frequent examples of naive literalism. That the Bible formed the basis of theological reflection for the Cappadocians can in no way be denied, but that they held to any particular style or styles of exegesis cannot be demonstrated.